Geology, geochemistry and mineral chemistry of campina do veado and santa blandina rapakivi granite stocks, southwest of sÃo paulo state - Godoy, Antonio Misson [UNESP]; Vieira, Otávio Augusto Ruiz Paccola [UNESP]; de Araújo, Larissa Marques Barbosa; de Godoy, Daniel Françoso [UNESP] (UNESP - Universidade Estadual Paulista, 2021)
The Campina do Veado and Santa Blandina granitic stocks are located in the southwest region of São Paulo state, in the municipality of Nova Campina, intrusive in the Itaiacoca Group's metavolcanosedimentary sequence rocks. These bodies are related to the evolution of neoproterozoic rapakivi granitogenesis northern part of Apiaí Terrain, Central Mantiqueira Province. The Campina do Veado rocks covers an area of approximately 20 km² and occur in the Taquari Guaçu river bed, at the Peripheral Depression Geomorphological Unit erosive buttresses, from Furnas and Itararé groups rocks of the Paraná Basin sedimentary sequence. The Santa Blandina stock of approximately 4 km2 is identified by small occurrences of isolated granitic rocks. The rocks are represented by pink to red color granitic varieties, a rare occurrence of gray, isotropic and porphyritic to equi-to inequigranular, with viborgitic varieties and presenting only biotite as mafic mineral. The rocks can be distinguished by monzogranitic, syenogranitic and alkali granite compositions, in addition to late aplitic and pegmatitic phases rocks. The granitic stocks magmatism demonstrates a strong relationship of similarities between its rocks, suggesting constituting the same body. These rapakivi granites are peraluminous belonging to the high potassium to shoshonitic calcium-alkaline series, Caledonian I-type, post-colisional to intra-plate anorogenic, highly differentiated, from the final magmatic arch construction phase or similar to A-type granites. It is correlated to shear zones transtensional structures at the end of Ribeira Orogenesis collisional event and reflects the stabilization of the Apiaí Terrain final geotectonic arrangement.
Geologia, geoquimica e quimica mineral dos stocks graníticos rapakivi campina do veado e santa blandina, sudoeste do estado de são paulo
Keywords: Campina do Veado Granite; Geochemistry; Mineral chemistry; Rapakivi; Santa Blandina Granite